PENERAPAN PROBLEM BASED LEARNING BERBASIS PEMBELAJARAN BERDIFERENSIASI DI SMAN 1 JEMBER UNTUK MENINGKATKAN HASIL BELAJAR - Rieneke Cahyani; Sawitri Komarayanti; Lilik Hidayah (ScienceEdu, 2023)
In 21st century learning requires humans to have the ability to think well, this learning must be able to trigger students' abilities to learn independently. Based on the observations of the class average value of 69.05, only 8 students reached the KKM or 23.52%. This research uses Classroom Action Research (PTK) which is conducted to improve the performance of educators regarding the quality of the learning process, and improve student learning outcomes through reflective action in the shape cycle. This research was conducted at SMAN 1 Jember with research in class X-9, totaling 34 students. The data collection technique used is a test (in the form of a written test/evaluation to collect data related to student learning outcomes). This research was conducted at SMAN 1 Jember from April to May 2023 with the material on Environmental Pollution and Accumulation of Pollutants in the Food Chain using the Problem Based Learning model based on differentiation learning. The application of a differentiated learner-based Problem Based Learning (PBL) model can improve student learning outcomes. This is shown from the results of variable data analysis. The results of data analysis on the student learning outcomes variable show that the proportion of completeness of student learning outcomes in cycle I has increased to 52.9% with an average value of 72.94, and continues to increase in the first cycle. II where the proportion of completeness of student learning outcomes reaches 94.10% with an average value obtained of 87.05